Shared Book-Reading in Early Childhood Education: Teachers’ Mediation in Children’s Communicative Development - Cárdenas, Karina; Moreno-Núñez, Ana; Miranda-Zapata, Edgardo (Frontiers in Psychology, 2020)
Fostering communicative skills in young children is core for their holistic development. Book reading activities have been evidenced as a valuable tool for supporting communicative exchanges between children and adults, but there is limited research on actual educational practices with children under 3 years old. This study explores teaching practices in Chilean early childhood education with children from 4 to 17 months of age. We focused on children’s performance of diverse communicative signs, as well as on the effect of the teacher’s mediation (signs and strategies) in a triadic shared-reading interaction (teacher-child-book). The study is part of a larger cross-sectional project. We conducted an experimental study following a pretest-posttest design with 11 children, who were randomly assigned to either the control or the experimental group. In addition, we conducted a six-week intervention on shared book reading between the pre- and posttest stages. We observed that children used a wide range of communicative signs when engaging in shared interactions with their teacher and different books. In the experimental group, children performed more communicative signs after participating in the intervention than at the beginning of the study. The reading experience that they gained through the intervention could explain the larger proportion of uses of the books, as compared to their control counterparts. Additionally, children performed different combinations of vocalizations, words, or repetitions within a single use. The conventional use of a book is not evident for an infant, and as such it requires of a systematic and semiotically mediated action of the adult to be consolidated. We conclude that offering preschool teachers a diverse selection of books enables them to better adjust to the particularities of each child. In this scenario educators are able to promote efficient spaces for children participation, increasing the complexity and variety of their communicative repertoire.